2008
DOI: 10.1175/2007jtecho542.1
|View full text |Cite
|
Sign up to set email alerts
|

Three-Way Error Analysis between AATSR, AMSR-E, and In Situ Sea Surface Temperature Observations

Abstract: Using co-locations of three different observation types of sea surface temperatures (SSTs) gives enough information to enable the standard deviation of error on each observation type to be derived. SSTs derived from the Advanced Along-Track Scanning Radiometer (AATSR) and Advanced Microwave Scanning Radiometer (AMSR-E) instruments are used, along with SST observations from buoys. Various assumptions are made within the error theory including that the errors are not correlated, which should be the case for thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
168
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(181 citation statements)
references
References 19 publications
13
168
0
Order By: Relevance
“…In regions where the SST variability is relatively low (e.g. between 5-25 • N and between 130 • E and 140 • W in the Pacific Ocean), the modelled SSTA is less than the observations by about 0.25-0.5 • C. O'Carroll et al (2008) suggested that the RMS of the measurement error of AMSR-E SST is about 0.42 • C. This indicates that in the regions where the SSTA variability is small (between 0.5-0.7 • C), the signal in the observations is likely to be dominated by measurement error because the signal-to-noise ratio is low. So the lowerthan-observed variability in the model may be an overestimate in the observed RMS, rather than an underestimate in the model.…”
Section: Sst Anomaly Comparisonsmentioning
confidence: 82%
“…In regions where the SST variability is relatively low (e.g. between 5-25 • N and between 130 • E and 140 • W in the Pacific Ocean), the modelled SSTA is less than the observations by about 0.25-0.5 • C. O'Carroll et al (2008) suggested that the RMS of the measurement error of AMSR-E SST is about 0.42 • C. This indicates that in the regions where the SSTA variability is small (between 0.5-0.7 • C), the signal in the observations is likely to be dominated by measurement error because the signal-to-noise ratio is low. So the lowerthan-observed variability in the model may be an overestimate in the observed RMS, rather than an underestimate in the model.…”
Section: Sst Anomaly Comparisonsmentioning
confidence: 82%
“…For instance, the lowest RSD of 0.180 K for the AATSR N3 retrieval is effectively the error in the in situ measurements and is comparable to the ~0.2 K drifter error found by O'Carroll et al (2008). The D3 retrieval, while it is more robust to atmospheric conditions and aerosol, does suffer from slightly elevated noise levels.…”
Section: Comparison With In Situmentioning
confidence: 53%
“…Although the above match-ups are not exactly coincident, their relatively similar global distribution and median differences allows us to adopt the approach of approach to O'Carroll et al (2008) and use multi-way statistics to estimate the uncertainty of comparing a single point in situ measurement to a 1-km AATSR pixel to be ~ 0.1 K.…”
Section: The Use Of Argo As a Reference Datasetmentioning
confidence: 99%
“…CC BY 4.0 License. O'Carroll et al (2008) compared three types of systems to measure sea-surface temperatures: two different radiometers and in situ observations from buoys. They discuss the assumption of the neglect of error correlations among the three data sets and the effect of representativeness errors.…”
Section: Summary and Discussion 20mentioning
confidence: 99%